2002
DOI: 10.1002/qua.10408
|View full text |Cite
|
Sign up to set email alerts
|

Density functional study of the redox processes in subphthalocyanines

Abstract: ABSTRACT:A theoretical investigation on the redox processes in the subphthalocyanines (SubPcs) was performed. Singly and doubly oxidative and reductive transformations were considered. The full geometry optimization of the participating molecules showed that the cone shape arrangement of the SubPc is preserved in their ionic derivatives even when two electrons are either donated or subtracted from the molecule. The biggest geometric changes under electron exchange processes were calculated for the BOCl bond di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 30 publications
7
30
0
Order By: Relevance
“…[28][29][30] This active space very well reproduces the electronic low-energy transitions of the SubPcs due to the breakdown of the Gouterman four level model observed in these compounds. Nevertheless, the expression for γ ijkl in a three level model is appreciably complex, and only in the case of reduced symmetry the final expression is manageable.…”
Section: Methodsmentioning
confidence: 84%
“…[28][29][30] This active space very well reproduces the electronic low-energy transitions of the SubPcs due to the breakdown of the Gouterman four level model observed in these compounds. Nevertheless, the expression for γ ijkl in a three level model is appreciably complex, and only in the case of reduced symmetry the final expression is manageable.…”
Section: Methodsmentioning
confidence: 84%
“…100 µs) 57. This stabilization is likely due to the particular characteristics of the axial polar bond of SubPc, which increases its length and ionic character upon SubPc reduction,58 and the donor–acceptor topology, which may prevent an efficient orbital overlap between the reduced SubPc LUMO and the oxidized Fc HOMO.…”
Section: Electron‐donor and ‐Acceptor Properties Of Phthalocyanines Amentioning
confidence: 99%
“…This approach has been used successfully in porphyrin‐related theoretical research 21. Because the SubPcs are molecular systems that are close to porphyrins, some workers 17, 18, 20 have performed DFT calculations with success. Considering the above‐mentioned elements, in the present study, the MSubPcs were fully optimized at the B3LYP/6‐31G* level 22, 23 with C 3 v symmetry.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Recently, quantum chemical calculations 16–20 have provided realistic high‐quality descriptions of the geometrical and electronic structures of SubPcs. Gong et al 18 reported that the geometries obtained at the B3LYP level were in much better agreement with the experiment data than obtained at the Hartree–Fock (HF) level with the same basis set.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation